Planned and reactive agility performance in semiprofessional and amateur basketball players - Lockie, R. G.; Jeffriess, M. D.; McGann, T. S.; Callaghan, S. J.; Schultz, A. B. (International Journal of Sports Physiology and Performance, 2014)
Context: Research indicates that planned and reactive agility are different athletic skills. These skills have not been adequately assessed in male basketball players. Purpose: To define whether 10-m-sprint performance and planned and reactive agility measured by the Y-shaped agility test can discriminate between semiprofessional and amateur basketball players. Methods: Ten semiprofessional and 10 amateur basketball players completed 10-m sprints and planned- and reactive-agility tests. The Y-shaped agility test involved subjects sprinting 5 m through a trigger timing gate, followed by a 45° cut and 5-m sprint to the left or right through a target gate. In the planned condition, subjects knew the cut direction. For reactive trials, subjects visually scanned to find the illuminated gate. A 1-way analysis of variance (P < .05) determined between-groups differences. Data were pooled (N = 20) for a correlation analysis (P < .05). Results: The reactive tests differentiated between the groups; semiprofessional players were 6% faster for the reactive left (P = .036) and right (P = .029) cuts. The strongest correlations were between the 10-m sprints and planned-agility tests (r = .590-.860). The reactive left cut did not correlate with the planned tests. The reactive right cut moderately correlated with the 10-m sprint and planned right cut (r = .487-.485). Conclusions: The results reemphasized that planned and reactive agility are separate physical qualities. Reactive agility discriminated between the semiprofessional and amateur basketball players; planned agility did not. To distinguish between male basketball players of different ability levels, agility tests should include a perceptual and decision-making component.